Automated feature detection and imaging for high-resolution screening of zebrafish embryos. (May 2011) - Peravali, Ravindra; Gehrig, Jochen; Giselbrecht, Stefan; Lütjohann, Dominic S.; Hadzhiev, Yavor; Müller, Ferenc; Liebel, Urban
The development of automated microscopy platforms has enabled large-scale observation of biological processes, thereby complementing genome scale biochemical techniques. However, commercially available systems are restricted either by fixed-field-of-views, leading to potential omission of features of interest, or by low-resolution data of whole objects lacking cellular detail. This limits the efficiency of high-content screening assays, especially when large complex objects are used as in whole-organism screening. Here we demonstrate a toolset for automated intelligent high-content screening of whole zebrafish embryos at cellular resolution on a standard wide-field screening microscope. Using custom-developed algorithms, predefined regions of interest—such as the brain—are automatically detected. The regions of interest are subsequently imaged automatically at high magnification, enabling rapid capture of cellular resolution data. We utilize this approach for acquiring 3-D datasets of embryonic brains of transgenic zebrafish. Moreover, we report the development of a mold design for accurate orientation of zebrafish embryos for dorsal imaging, thereby facilitating standardized imaging of internal organs and cellular structures. The toolset is flexible and can be readily applied for the imaging of different specimens in various applications.